(3Pjd dhGbM GdCfhGQ GdbOSjI aj WHbGJ GdYdeGA hGdUhajIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , PcQ ajg LeGYI ef eTGjN eUQ GdeYGUQjf dg s
(3BNQgG (B:s
(3hHbjI GUMGHfG PcQfGge ai cJGHfG GdeaGNQ hGdeBKQ ai YdeGA GdbQf GdYGTQ , Ke bGd (B/ (3hdjcf gPG BNQ cJGHfG GdeSei HdhGbM GdCfhGQ GdbOSjI ai WHbGJ (B( (3efGbH(B) (3GdYdeGA GdUhajI , Edi SfI (B961 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B140 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B513) s
Keywords: (3GdJGQjNs